2010
DOI: 10.1097/wad.0b013e3181b4f736
|View full text |Cite
|
Sign up to set email alerts
|

ASL Perfusion MRI Predicts Cognitive Decline and Conversion From MCI to Dementia

Abstract: We compared the predictive value of cerebral perfusion as measured by arterial-spin labeling magnetic resonance imaging (ASL-MRI) with MRI-derived hippocampal volume for determining future cognitive and functional decline and subsequent conversion from mild cognitive impairment to dementia. Forty-eight mild cognitive impairment subjects received structural and ASL-MRI scans at baseline and clinical and neuropsychologic assessments annually. Thirteen subjects became demented during the period of longitudinal ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
167
5
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(186 citation statements)
references
References 66 publications
12
167
5
2
Order By: Relevance
“…Furthermore, both CBF reduction (Hirao et al, 2005;Caroli et al, 2007;Hansson et al, 2009;Johnson et al, 1998;Kitagawa et al, 2009;Chao et al, 2010) and deficits in the reactivity of cerebral vessels to hypercapnia (vasoreactivity to hypercapnia (VR h )) forecast cognitive decline (Silvestrini et al, 2006). It has been thus proposed that preexisting vascular risk factors mechanistically contribute to cognitive deterioration by directly compromising cerebral blood supply, especially in the states of increased demand.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, both CBF reduction (Hirao et al, 2005;Caroli et al, 2007;Hansson et al, 2009;Johnson et al, 1998;Kitagawa et al, 2009;Chao et al, 2010) and deficits in the reactivity of cerebral vessels to hypercapnia (vasoreactivity to hypercapnia (VR h )) forecast cognitive decline (Silvestrini et al, 2006). It has been thus proposed that preexisting vascular risk factors mechanistically contribute to cognitive deterioration by directly compromising cerebral blood supply, especially in the states of increased demand.…”
Section: Introductionmentioning
confidence: 99%
“…7,[22][23][24] However, we are unaware of any existing studies in ADAD exploring CBF. The few studies using FDG-PET in ADAD have demonstrated decreased areas of metabolism, mostly in the temporal and parietal heteromodal cortices in asymptomatic to mildly symptomatic subjects.…”
mentioning
confidence: 99%
“…Abnormal cerebral perfusion are clear indicators of diagnostic transition from MCI to AD [65,66]. Borroni and Chao et al, has demonstrated patterns of hypoperfusion in parietal, temporal and posterior cingulate cortex in all those patients who are progressing from MCI to AD [67,68]. Another study performed by Caroli et al, compared three diagnostic groups namely CN, MCI and AD.…”
Section: Perfusionmentioning
confidence: 99%